GAMBARAN TINGKAT KECEMASAN PADA MAHASISWA KEPANITERAAN KLINIK DI ERA PANDEMI COVID-19 TAHUN 2022 - Santy Mail; Laura Huwae; Amanda G. Manuputty; Parningotan Y. Silalahi; Presly G. Siahaya; Johan B. Bension (Fakultas Kedokteran Universitas Pattimura, 2023)
The clinical clerkship is one part of basic medical education and is an advanced stage to complete the medical professional education program. In dealing with COVID-19, medical personnel are at the forefront. It is not an easy thing to organize clinical clerkship activities for Medical Professional Education Students while continuing to stay at the hospital during the COVID-19 pandemic. Clinical clerkship students will sacrifice time, thought, and energy to prevent the spread of COVID-19. This condition places clinical clerkship students under the threat of psychological disorders such as anxiety. The purpose of this study was to describe the level of anxiety in clinical clerkship students in the COVID-19 pandemic era in 2022. The method used was cross-sectional on clinical clerkship students, Faculty of Medicine, University of Pattimura, with a total sample of 114 respondents. The analysis used is univariate analysis. The questionnaire used in this study was the SAS/SRAS (Zung Self Rating Anxiety Scale) questionnaire. The results showed as many as 35.1% of students experienced moderate anxiety and 16.7% of students experienced severe anxiety. The results of the research based on gender found that male respondents had a mild level of anxiety, namely 19 people (16,7%), and female gender had an anxiety level in the moderate category, reason, 36 people (31,6%). The results also show that based on where they live with their parents, most of them have an anxiety level in the moderate category, as many as 31 people (27,2%) and those who live alone (not with their family) most of them have an anxiety level in the mild category, namely as many as 25 people (21,9%). Based on the location of the rotation, the respondents were located at RSUD Dr. M. Haulussy mostly has an anxiety level in the severe category, namely as many as 19 people (16,7%); at Regional Special Hospitals (RSKD) Maluku Province mostly has an anxiety level in the mild category, namely 4 people (3,5%); at Regional General Hospital dr. H. Ishak Umarella mostly has an anxiety level in the moderate category, namely as many as 5 people (4,4%); at Al-Fatah General Hospital mostly has an anxiety level in the mild category, namely 6 people (5,3%); at Level II General Hospital Prof. dr. J. A. Latumeten Ambon mostly has an anxiety level in the moderate category, namely 7 people (6,1%); as well as the respondents whose rotation locations is at Sumber Hidup-GPM Hospital, most of them had a moderate level of anxiety, namely as many as 8 people (7,0%).